Advancing child nutrition science in the scaling up nutrition era: a systematic scoping review of stunting research in Guatemala. Issue 1 (31st December 2019) - Cordon, Ana; Asturias, Gabriela; De Vries, Thomas; Rohloff, Peter
Abstract : Introduction: Ever since the 1960s, Guatemala has been a principle site for global academic research on child growth and nutrition. Nevertheless, Guatemala still has one of the highest rates of child stunting in the world. Since 2012, Guatemala has had a comprehensive national policy on stunting, calling for a renewed investment in innovative, multilevel nutrition interventions and implementation science. Our objective was to perform a systematic search and scoping review of the literature on stunting in Guatemala to identify gaps in research and opportunities for responding to this unique policy opportunity. Methods: We conducted a systematic search and scoping review on stunting in Guatemala, searching the PubMed, Web of Science and PsycINFO databases. Eligible articles were of any design or format, published in English and Spanish from 2000 to 2018. Articles were thematically grouped by those published before (2000–2011) and after (2012–2018) the new national policy initiatives. Results: We identified a total of 1934 articles through database searches. After full-text review, 104 were included in the synthesis. The volume of published articles on stunting increased from a mean of 3.2 to 9.4 articles/year before and after 2012. There was a shift toward articles generating new data on priority populations, including rural indigenous Maya populations (34% vs 61%, χ 2 test, p=0.01). However, the proportion of studies conducting implementation evaluations or testing new interventions was low and did not change significantly (34% vs 18%, χ 2 test, p=0.07). Among 17 identified intervention studies, only 4 tested multilevel interventions, and there were no published interventions incorporating nutrition-sensitive interventions. Conclusions: A systematic search and scoping review of the literature on child stunting in Guatemala identified critical opportunities for new research in multilevel interventions, nutrition-sensitive interventions and implementation science.